2018
DOI: 10.1253/circj.cj-17-0247
|View full text |Cite
|
Sign up to set email alerts
|

Barthel Index and Outcome of Open Bypass for Critical Limb Ischemia

Abstract: It is not BI at admission, but BI at discharge that determines long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…47 BI has an important impact on the prognosis and mortality of patients, which has been verified in postoperative patients and patients with acute heart failure. 11,13 A Danish cohort study based on the geriatric database explored the relationship between BI and mortality in elderly patients. The results showed that BI was negatively correlated with the mortality of patients, and the higher the BI score, the lower the mortality of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…47 BI has an important impact on the prognosis and mortality of patients, which has been verified in postoperative patients and patients with acute heart failure. 11,13 A Danish cohort study based on the geriatric database explored the relationship between BI and mortality in elderly patients. The results showed that BI was negatively correlated with the mortality of patients, and the higher the BI score, the lower the mortality of patients.…”
Section: Discussionmentioning
confidence: 99%
“…20 In our study, the BI cut-off value of patients divided into two groups was 60, which was consistent with previous studies. [11][12][13][14]21 Statistical Analysis R 3.3.2 statistical software was used to perform all analyses. For measurement data, the normality of data was tested using the Shapiro test.…”
Section: Data Collection and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Numerous studies have showed that hospitalizations for acute diseases are related to a decline in BI scores and that functional disability is associated with poor outcomes in patients with stroke, acute coronary syndrome, and peripheral artery disease. [12][13][14] with the patient or family approximately 2 weeks before admission, as in a previous study. 15 Post-BI was defined as BI measured at discharge.…”
mentioning
confidence: 99%
“…These variables are reportedly independent predictors for ischemic wound healing or life-threatening outcomes in patients who undergo open bypass for critical limb ischemia. 21,22) Therefore, these factors might be helpful in deciding on MFC.…”
Section: Discussionmentioning
confidence: 99%